Designing a system to protect public and private facilities from fires and theft by using Arduino and its peripherals (Faculty of Education Scientific Journal, 2024)
This research demonstrates the importance of using modern technology as an auxiliary, effective, and essential factor in monitoring and protecting homes and public and private institutions. This research aims to build a smart system capable of taking a set of precautionary measures in the event of any theft or fire being detected without human intervention, which provides a timely opportunity to deal with this incident, thus, providing a protection system from theft and fires. This importance extends to its evident impact on establishing security and confirming protection for facilities. This was evident through simulating reality using the (Proteus) program, which simulates practical applications in nature (due to the lack of capabilities required for that). There have been many cases of theft and fires that had dire consequences, so a theoretical protection system was implemented that relied on sensors that send signals to the property owner. The program (Proteus) used in simulating reality also stressed the need to use tangible protection devices and their algorithms in practical application.  The research results show that using electronic protection devices, such as sensors, helps immensely spread security, safety, and awareness nationwide at large at a low cost. The reason behind this is its effectiveness in early warning and issuing messages to real estate owners in case of sensing danger, The research also suggested conducting several studies related to the research subject, which is protection and security. The competent authorities should take care of the issue by providing and supporting the required equipment, training and preparing specialized cadres.
Keywords: GSM; Sensor; Automation; Electronic System; Arduino; Smart Hose